2008
DOI: 10.1021/ef800577j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biodiesel Using Microwave Absorption Catalysts

Abstract: To enhance the synthesis process for biodiesel (fatty acid methyl ester, FAME), microwave absorption solid acid catalysts were used for transesterification under microwave radiation. The H 2 SO 4 /C catalyst was prepared by an impregnation method. The surface areas of active carbon and H 2 SO 4 /C were measured by the BET method. Synthesis reactions were carried out under different conditions using castor oil and methanol as the feedstock. The amounts of FAME in the product were analyzed by high-performance li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 19 publications
3
49
0
Order By: Relevance
“…Many studies reported that compared to coconut oil, transesterification of castor oil requires higher temperature 10 and higher methanol to oil ratio [11][12] . In an attempt to circumvent these problems, in this current study transesterification of castor oil was carried out using coconut oil as coreactant.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that compared to coconut oil, transesterification of castor oil requires higher temperature 10 and higher methanol to oil ratio [11][12] . In an attempt to circumvent these problems, in this current study transesterification of castor oil was carried out using coconut oil as coreactant.…”
Section: Introductionmentioning
confidence: 99%
“…In practice a higher molar ratio is needed for the reaction, because the transesterification reaction is reversible. Furthermore, biodiesel and glycerol are miscible due to the use of excess methanol [13,14]. However methanol is strong medium for absorbing microwaves, and thus the excess methanol may absorb microwave energy and reduce the microwave power [9].…”
Section: The Effects Of Molar Ratio With Oil To Methanolmentioning
confidence: 99%
“…Since the reaction is reversible, excess alcohol is used to shift the equilibrium to the product side (Fangrui and Milford, 1999). Under Transesterification reaction with alcohol the first step is the conversion of triglycerides to diglycerides, which is followed by the subsequent conversion of higher glycerides to lower glycerides and then to glycerol, yielding one methyl ester molecule from each glyceride at each step (Hideki et al, 2001 Several examples of microwave irradiated transesterification methods have been reported using homogenous alkali catalyst Azcan and Danisman, 2008), acid catalyst (Mazo and Rios, 2010a) and heterogeneous alkali catalyst , heterogeneous acid catalyst (Yuan et al, 2009) and enzymatic . Microwave synthesis is not easily scalable from laboratory small-scale synthesis to industrial multi kilogram production.…”
Section: Transesterification Reactions Assisted By Mwmentioning
confidence: 99%